Prevalence of Diarrhoea and its association with Wasting, Age, and Gender in Children below the Age of Five years - Gupta, Anil (International Journal of Medical Research and Review, 2014)
Introduction: Diarrhea is the leading cause of malnutrition in children below the age of five. Materials and Methods: Present work consisted of total 440 children, selected by random multi-stage sampling method, based on sample selection criteria, executed in city, Fazilka, Punjab. Results and Discussion: The study showed overall prevalence of (5.5%, 24/440 ) diarrhea in whole study participants and high prevalence of (41%, 24/58) diarrhea in children, who had acute malnutrition (wasting) and it was accompanied by highly significant (p<0.001), association between diarrhea and wasting in children. The prevalence of diarrhoea was found to be associated with age (p<0.001), showed high prevalence (12%) in lower age group (2y-3y) in comparison to its low prevalence (2.7%) in higher age group (>3y-4y). Males children had less prevalence (5.4%) of diarrhea as compared with female children (5.5%), not statistically significant (p=0.5). Conclusion: Diarrhea is invariably linked with age and acute malnutrition in children.